Intimate partner violence in pregnant women living with HIV in South Africa: prevalence and associated factors - Mkwakwami, Kudzai (Department of Public Health and Family Medicine, 2026)
Introduction Intimate partner violence (IPV) is a significant public health problem that affects individuals across the world, of all ages, genders, and socio-economic backgrounds. In South Africa, the prevalence of IPV among pregnant women is high. This study aims to investigate the prevalence and associated factors of IPV among pregnant women living with HIV in Cape Town, South Africa. Methods We used a cross-sectional design, with data collected through face-to-face interviews at enrolment into a larger study (CareConekta NCT03836625). Using a structured questionnaire, data were collected on sociodemographic characteristics, IPV (measured using the World Health Organisation Violence Against Women questionnaire) and antiretroviral therapy (ART) adherence (using a combined three-item self-reported adherence score where 100 presents perfect adherence). Results Among 197 pregnant women living with HIV, the prevalence of IPV was 43.2%. The most common form of IPV reported was emotional abuse (30.7%), followed by physical abuse (24.5%) and sexual abuse (10.5%). There was also an overlap in IPV experiences observed amongst participants where 32% of women with any IPV reported both physical and emotional abuse, 4% both emotional and sexual and 13% reported all three forms of IPV. Higher poverty score was identified as a factor associated with an increased risk of experiencing IPV (OR= 0.72, 95% CI = 0.32-1.59). In this cohort, 20% of women had perfect self-reported adherence and women who did not experience IPV had higher odds of perfect ART adherence compared to those who had experienced any form of IPV (OR= 1.09, 95% CI = 0.47, 2.39). Conclusion We found that the prevalence of IPV among pregnant women living with HIV in Cape Town, South Africa was very high in all three domains and these findings are consistent with existing literature. The high prevalence of IPV among this population highlights the need for interventions to prevent IPV and to support women experiencing IPV in pregnancy. In this analysis the experience of IPV was associated with poor ART adherence. Experiencing IPV adds on to the challenges and the burden of women living with HIV and it contributes to a plethora of health challenges and complications. Asking women about IPV experiences during antenatal care could be an important intervention to facilitate support for women experiencing IPV in pregnancy.